Associated factors for the utilization of institutional delivery services in Nepal: Findings from the Nepal Demographic Health Survey, 2022 - Om Chandra Thasineku; Sudesh Pandit; Devaraj Acharya; Yogendra Bahadur Gurung (PLoS ONE, 2025)
Introduction Institutional delivery provides skilled obstetric health care, postnatal care, and essential medical timely intervention to enhance the health of mothers and children. In Nepal, the proportion of institutional deliveries has increased from 8 percent in 1996–79 percent in 2022, although it is not satisfactory. This study investigates disparities in the utilization of institutional delivery service across associated factors related to residential factors, socio-economic factors, health service-related factors, and bio-demographic factors. Methods We used secondary data from the Demographic and Health Survey (DHS) 2022 of Nepal. It involves a sample of 1977 eligible women aged 15–49 who had given birth within two-year preceding the survey. We considered institutional delivery as an outcome variable, while residential, socio-economic, bio-demographic, and health service-related factors as independent variables. Descriptive analysis and binary logistic regression analysis for crude and adjusted odds ratios (AOR) along with 95% confidence interval (CI) were utilized. Results Of the total 1977 women, 1569 (79.4%) opted for institutional delivery. Women belonging to the Muslim ethnic group had lower odds (AOR:0.500, 95% CI: 0.259–0.966, p < 0.050) compared to their reference group. Similarly, the likelihood of opting for institutional delivery was significantly lower among women who required more than 30 minutes time to reach a health facility (AOR:0.626, 95% CI: 0.491–0.800, p < 0.001) and those having 6 + parity (AOR:0.080, 95% CI: 0.032–0.205, p < 0.001) compared to their reference group. In the contrary, women from Terai region (AOR:2.428, 95% CI: 1.194–4.937, p < 0.050), Bagmati Province (AOR:2.327, 95% CI: 1.179–4.593, p < 0.050), secondary and higher education level (AOR:3.161, 95% CI: 2.141–4.668, p < 0.001), richest wealth group (AOR:13.451, 95% CI: 5.231–34.589, p < 0.001), and antenatal care (ANC) visits 4 and more times (AOR:5.084, 95% CI: 2.7963–9.242, p < 0.001), were noticed more likely to choose for institutional delivery compared to their reference group, respectively. Conclusion The result shows the ecological region, province, ethnic group, distance to reach health facility, parity, respondents’ education level, wealth index and ANC visits, and mother’s age in 5-year groups are the associated factors for the utilization of institutional delivery service in Nepal. It highlights the need for targeted interventions to enhance the utilization of institutional delivery services. Addressing socio-economic and geographical disparities, economic barriers, advancing education, promoting antenatal care visits, and ensuring nearer healthcare accessibility are crucial to achieving the equitable maternal and neonatal health care through institutional delivery in Nepal. It is concluded that more attention needs to be paid to areas where the severity persists by professionals and policymakers as well.